2014
DOI: 10.3389/fnbeh.2014.00226
|View full text |Cite
|
Sign up to set email alerts
|

Is neural hyperpolarization by cathodal stimulation always detrimental at the behavioral level?

Abstract: Cathodal transcranial direct current stimulation (c-tDCS) is usually considered an inhibitory stimulation. From a physiological perspective, c-tDCS induces hyperpolarization at the neural level. However, from a behavioral perspective, c-tDCS application does not always result in performance deterioration. In this work, we investigated the role of several important stimulation parameters (i.e., timing, presence of pauses, duration, and intensity) in shaping the behavioral effects of c-tDCS over the primary visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 73 publications
3
63
2
Order By: Relevance
“…By contrast, we know of no account that generates behavioural predictions of the effect of gross polarisation of cortex (Box 3). In support of this, behavioural improvements have also been reported for so-called cathodal stimulation [6,47]. Moreover, suppression of function in one region may even improve behavioural outcomes ('paradoxical facilitation').…”
Section: Anodal Currents Increase Excitability Cathodal Decrease Excmentioning
confidence: 88%
“…By contrast, we know of no account that generates behavioural predictions of the effect of gross polarisation of cortex (Box 3). In support of this, behavioural improvements have also been reported for so-called cathodal stimulation [6,47]. Moreover, suppression of function in one region may even improve behavioural outcomes ('paradoxical facilitation').…”
Section: Anodal Currents Increase Excitability Cathodal Decrease Excmentioning
confidence: 88%
“…Teo et al (2011) found that increasing both stimulation strength and duration was required to reliably enhance working memory: Only during the last 5 min of stimulation (i.e., 15-20 min) at 2 mA, RTs were significantly reduced compared to baseline, while for the 1 mA condition the effect did not reach significance, but was largest during the preceding 5 min (i.e., 10-15 min). Pirulli et al (2014), on the other hand, found that while shortening duration of off-line stimulation of visual cortex from 22 min to 9 min hardly affected performance in a visual orientation task, reducing intensity from 1.5 mA to 0.75 mA abolished the effect on behavioural outcome measures.…”
Section: Tdcs Stimulation Strength and Durationmentioning
confidence: 93%
“…However, in studies of cognition this dichotomy is less frequently observed Jacobson et al, 2012;Sparing et al, 2009;Stone and Tesche, 2009) in particular with respect to cathodal tDCS. While anodal tDCS most consistently shows an improvement (Boggio et al, 2010;Cerruti and Schlaug, 2009;Chi et al, 2010;Flöel et al, 2008;Fregni et al, 2005;Iyer et al, 2005;Kincses et al, 2004;Kraft et al, 2010;Sparing and Mottaghy, 2008) or no change in cognitive tasks Karim et al, 2010;Monti et al, 2008;Rogalewski et al, 2004;Varga et al, 2007), cathodal tDCS may deteriorate Berryhill et al, 2010;Karim et al, 2010;Rogalewski et al, 2004;Varga et al, 2007) as well as enhance (Monti et al, 2008;Moos et al, 2012;Pirulli et al, 2014;Weiss and Lavidor, 2012) performance in healthy participants. It has been suggested that in the latter studies cathodal tDCS might have improved performance by decreasing neuronal competition , acting like a noise filter particularly in highloaded scenes (Weiss and Lavidor, 2012).…”
Section: Tdcs Polarity Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…So, if cognitive control in general had been impaired by cathodal stimulation of the pFC , task performance should have suffered in both the Simon and the SNARC task, leading to generally increased conflict effects. Here, in this respect, tDCS was ineffective, possibly undermined by compensatory processes (Pirulli, Fertonani, & Miniussi, 2014) or by the intermediate role of dorsolateral pFC (i.e., as compared with the ACC; Botvinick et al, 2004) during nonemotional conflict processing (i.e., as compared with emotional processing; . Similar behavioral results have been obtained from applying tDCS over medial pFC during an Eriksen flanker conflict task, that is, there was no modulation of executive attention from 2 mA anodal tDCS (Coffman, Trumbo, & Clark, 2012).…”
Section: Functional Implications Of Pfc In Number Processingmentioning
confidence: 94%